Kuantifikasi Bakteri Pelarut Phosphate pada Media Sisa Rotasi Tanam Dengan Aplikasi Biofertiliser-VP3 Terhadap Pertumbuhan Bibit Tomat : Biofertiliser-VP3, Rotasi Tanaman, Tanah Berpasir - Sari, Sekar Arum Dwi Kartika; Arfarita, Novi; Qur'ania, Anita (Universitas Islam Malang, 2025)
The physical and chemical conditions of sandy soil do not support plant growth require improvement through the addition of biofertilizers and microorganisms. This study aims to determine the effect of soybean-mustard crop rotation on the abundance of phosphate-solubilizing bacteria, as well as the growth of tomato seedlings in post-mining sand growing media with the addition of VP3 and Trichoderma viride FRP3 biofertilizers. The study was conducted for four months using a Completely Randomized Design with six treatments and four replications. Observed parameters included soil chemical properties (pH), bacterial total plate count (TLC), and tomato seedling growth. The results showed that the combination treatment of VP3 biofertilizer pellets, organic matter, and Trichoderma viride (V2 and V4) significantly increased the number of phosphate-solubilizing bacteria compared to the control. The V4 treatment also produced the highest tomato seedling height, reaching 39.15 cm at 8 days after planting (DAP), although there were no significant differences in fresh weight, number of leaves, and root length. The soil nutrient content in treatments V1–V4 was categorized as moderate to high, with a neutral soil pH. The results of this study indicate that the planting medium used in soybean-mustard rotation enriched with VP3 and Trichoderma viride biofertilizer has the potential to be applied sustainably to support suboptimal land agriculture, especially sandy soil. Keywords: Biofertilizer-VP3, Crop Rotation, Sandy Soil